A Compositionally Tunable Micelle Platform for Integrated Photoacoustic Imaging, Direct Visual Guidance, and Photothermal Therapy of Solid Tumors - Jennifer Ferd; Ariane Rocha Bartolomeu; Nicole Carrillo-Malani; Qiushi Liang; Maryam Soleimani; Daniela Araiza-Olivera; Margie L. Clapper; Joann Miller; Theresa M. Busch; Zhiliang Cheng; Andrew Tsourkas; Ahmad Amirshaghaghi (ACS Applied Nano Materials, 2026)
Abstract Incomplete tumor resection remains a primary driver of cancer recurrence and would benefit from technologies that enable both accurate tumor delineation and localized ablation of residual disease. Here, we report a compositionally tunable nanotheranostic platform based on sub-50 nm (∼40–50 nm) poly(ethylene glycol)-block-poly(caprolactone) (PEG-PCL) nanoscale micelles coloaded with phthalocyanine (Pc) and naphthalocyanine (Nc) dyes, designed for integrated photoacoustic (PA) imaging, direct visual guidance, and photothermal therapy (PTT). By incorporating a tetra-tert-butyl-substituted zinc phthalocyanine (ZnPc(TB)) and an octabutoxy-substituted copper naphthalocyanine (CuNc(Octa)) into micelles via both coencapsulation and postformulation mixing, we achieved an optimized 80:20 ZnPc(TB):CuNc(Octa) ratio that balances blue tumor coloration with high-contrast PA signals and efficient photothermal conversion. In vivo evaluation in orthotopic triple-negative breast cancer and spontaneous colorectal tumor models demonstrated that these micelles accumulate sufficiently in tumors to enable PA mapping, followed by real-time visual identification of tumor margins under white light, and efficient photothermal ablation. Notably, no difference was observed between the coencapsulated and mixed formulations. Comprehensive hematologic analysis confirmed the platform’s safety, with observed shifts attributable to procedural stress and tumor-associated physiology rather than to treatment-specific effects. These findings establish multichromophore Pc/Nc micelles as a versatile platform in which optical signatures can be rationally tuned to bridge the gap between deep-tissue detection, intraoperative guidance, and tumor eradication, offering a nanoscale, translatable strategy for applications such as intraoperative surgical margin assessment during breast-conserving surgery and endoscopic identification and ablation of colorectal adenomas.